If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7y + 2)(y + -5) = 0 Reorder the terms: (2 + 7y)(y + -5) = 0 Reorder the terms: (2 + 7y)(-5 + y) = 0 Multiply (2 + 7y) * (-5 + y) (2(-5 + y) + 7y * (-5 + y)) = 0 ((-5 * 2 + y * 2) + 7y * (-5 + y)) = 0 ((-10 + 2y) + 7y * (-5 + y)) = 0 (-10 + 2y + (-5 * 7y + y * 7y)) = 0 (-10 + 2y + (-35y + 7y2)) = 0 Combine like terms: 2y + -35y = -33y (-10 + -33y + 7y2) = 0 Solving -10 + -33y + 7y2 = 0 Solving for variable 'y'. Factor a trinomial. (-2 + -7y)(5 + -1y) = 0Subproblem 1
Set the factor '(-2 + -7y)' equal to zero and attempt to solve: Simplifying -2 + -7y = 0 Solving -2 + -7y = 0 Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -7y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -7y = 0 + 2 -7y = 0 + 2 Combine like terms: 0 + 2 = 2 -7y = 2 Divide each side by '-7'. y = -0.2857142857 Simplifying y = -0.2857142857Subproblem 2
Set the factor '(5 + -1y)' equal to zero and attempt to solve: Simplifying 5 + -1y = 0 Solving 5 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1y = 0 + -5 -1y = 0 + -5 Combine like terms: 0 + -5 = -5 -1y = -5 Divide each side by '-1'. y = 5 Simplifying y = 5Solution
y = {-0.2857142857, 5}
| 8x(8+6x)=20 | | .25(12x)=.6+.35x | | -2(x-4)=-6(2+x) | | 5(x+1)+51=-2x | | 4x+14=6x-26 | | 2m+7(m-1)=-21-5m | | 5+6y=5y+10 | | -abx^2+bcx+1=0 | | 5+y^2+7=3 | | 15w-22=-111 | | 8v+4=2v-8 | | 4(x-4)+2x=4x-6 | | (6y+5)(y-2)= | | 13x+7=6x+14 | | -3+7q=-7+9q | | -(1+6m)+6m=-11+3(r-7) | | Y=(5t^2)*(5t^3) | | -2(3)(-5)= | | 3(7-4x)=-39 | | 12=96 | | 3x+3+55=180 | | 4(5x-7)=52 | | 4x^3-34x^2+70x-25=0 | | -5s-9=-2s | | 2x^2-12x=32x-192 | | 3(-7+7x)=168 | | 5(8-8x^2)=8 | | 6y-28=4y-12 | | -7u=-8u+6 | | f(x)=ln(x+1) | | 12x+36=-3x-81 | | -6-5x=4x-51 |